2019
DOI: 10.4034/pboci.2019.191.27
|View full text |Cite
|
Sign up to set email alerts
|

Excess Body Weight, Snack Limits and Dental Caries in Brazilian Preschoolers: A Population-Based Study

Abstract: Objective: To evaluate the relationship between excess body weight (EBW) and the prevalence of dental caries in preschoolers considering parental control regarding snack consumption. Material and Methods: An observational, population-based, cross-sectional study was conducted at Municipal Child Education Centers in the city of Curitiba, Brazil, involving a representative sample of 686 preschool children aged four to five years and eleven months and their parents/caregivers. Dental caries was analyzed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…1 ). 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 The references of all reports of included studies is listed in the Supplementary Material Appendix 1 and the reason for exclusion of the 222 studies assessed for data extraction is listed in Supplementary Material Appendix 2.
Figure 1 Process of selection and inclusion of studies in the systematic review.
…”
Section: Resultsmentioning
confidence: 99%
“…1 ). 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 The references of all reports of included studies is listed in the Supplementary Material Appendix 1 and the reason for exclusion of the 222 studies assessed for data extraction is listed in Supplementary Material Appendix 2.
Figure 1 Process of selection and inclusion of studies in the systematic review.
…”
Section: Resultsmentioning
confidence: 99%
“…Tw e n t y -t h r e e s t u d i e s t e s t e d t h e association bet ween overweight and dental caries. 12,36,29,30,32,34,35,37,39,43,44,47,48,52,53,[55][56][57][58][59][60][61]66 Of these, 21 found no association between the two variables investigated in children/adolescents. 12,36,29,30,32,34,37,39,[43][44][45]48,[51][52][53][56][57][58][59][60]66 Three studies concluded that overweight children/ adolescents were less likely to exhibit dental caries than their normal weight peers.…”
Section: Results Of Individual Studies Overweight Vs Dental Cariesmentioning
confidence: 94%
“…12,36,29,30,32,34,35,37,39,43,44,47,48,52,53,[55][56][57][58][59][60][61]66 Of these, 21 found no association between the two variables investigated in children/adolescents. 12,36,29,30,32,34,37,39,[43][44][45]48,[51][52][53][56][57][58][59][60]66 Three studies concluded that overweight children/ adolescents were less likely to exhibit dental caries than their normal weight peers. 47,55,61 Obesity vs. dental caries Twenty-three studies tested the association between obesity and dental caries.…”
Section: Results Of Individual Studies Overweight Vs Dental Cariesmentioning
confidence: 94%
See 2 more Smart Citations